2016
DOI: 10.1007/s12072-016-9760-3
|View full text |Cite
|
Sign up to set email alerts
|

Asian-Pacific Association for the Study of the Liver (APASL) consensus guidelines on invasive and non-invasive assessment of hepatic fibrosis: a 2016 update

Abstract: Hepatic fibrosis is a common pathway leading to liver cirrhosis, which is the end result of any injury to the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
147
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(165 citation statements)
references
References 195 publications
0
147
0
12
Order By: Relevance
“…1,2 Regarding the lack of liver biopsy in all the patients, we do agree that several noninvasive markers are available for evaluating HBV infection-related fibrosis 3,4 and that it should be better to have a liver biopsy in all the patients. Although all the patients had either a liver biopsy or a noninvasive evaluation at the beginning of medical care, we had to take into account a risk of misclassification which could have been dually increased by the discrepancies observed between noninvasive fibrosis markers and the significant decrease in fibrosis scores linked to viral suppression but also to a potential deterioration related to liver comorbidities.…”
Section: Authors' Replymentioning
confidence: 95%
See 1 more Smart Citation
“…1,2 Regarding the lack of liver biopsy in all the patients, we do agree that several noninvasive markers are available for evaluating HBV infection-related fibrosis 3,4 and that it should be better to have a liver biopsy in all the patients. Although all the patients had either a liver biopsy or a noninvasive evaluation at the beginning of medical care, we had to take into account a risk of misclassification which could have been dually increased by the discrepancies observed between noninvasive fibrosis markers and the significant decrease in fibrosis scores linked to viral suppression but also to a potential deterioration related to liver comorbidities.…”
Section: Authors' Replymentioning
confidence: 95%
“…1 However, different non-invasive markers of fibrosis have different sensitivity and specificity in staging liver fibrosis. [2][3][4] In the study, the authors analysed the comorbidities such as arterial hypertension and diabetes among different groups. 1 However, the coexistences with other comorbidities such as nonalcoholic fatty liver diseases were not described by the authors.…”
mentioning
confidence: 99%
“…Liver biopsy is the gold standard for the evaluation of the degree of fibrosis [24,25]. However it can show some limits due to sampling related to inter operator variability [26], risk of tumor seeding when associated to biopsy for lesion diagnosis [27] and finally because it's invasive even through a trans jugular access with less morbidity [28]. Serum biomarkers are used and give moderate estimation of liver fibrosis [29] comparable to given information by liver biopsy in main chronic liver disease.…”
Section: Assessment Of Fibrosis and Cirrhosismentioning
confidence: 99%
“…The Asian-Pacific Association suggested Fibro test to be accurate for the Study of the Liver on its 2016 guideline beside AST platelet ratio index (APRI). The last one is especially useful in resourcelimited conditions [26]. Improvement in imaging technique and recent publications suggest that magnetic resonance elastography [30] and Acoustic radiation force impulse imaging ARFI [30] allows nowadays to perform a good assessment of liver fibrosis with high sensitivity and specificity.…”
Section: Assessment Of Fibrosis and Cirrhosismentioning
confidence: 99%
“…Fibrosis causes an increase of liver stiffness that can be measured using non-invasive methods. Nowadays, with the availability of direct acting antiviral agents that are highly effective for the eradication of the hepatitis C virus (HCV), the histological staging of liver fibrosis is no longer crucial for starting the treatment of patients with chronic hepatitis C. In fact, non-invasive methods have been accepted also by clinical guidelines [2,3]. The guidelines of the European Association for the Study of the Liver (EASL), produced together with the Asociación Latinoamericana para el Estudio del Hígado (ALEH), have suggested that in patients with viral hepatitis there are two clinically relevant endpoints: the detection of significant fibrosis and the detection of cirrhosis [2].…”
Section: Introductionmentioning
confidence: 99%